Subclavian pseudoaneurysm presenting as partially obstructed airway - Muhammad J. Khan (17877005) (2023)
We are presenting a noteworthy instance of managing the airway of a patient who had acute tracheal stenosis of considerable magnitude caused by external compression resulting from a large right subclavian pseudoaneurysm. Tracheal compression resulting from an aneurysm is an infrequent occurrence and has been reported in the literature in a limited number of case reports. The reported cases have been attributed to thoracic aortic aneurysm, aortic notch or left subclavian aneurysm. However, the current case study is the first of its kind to describe a right subclavian artery pseudoaneurysm leading to a narrowing of the tracheal lumen by over 70%. The patient presented to our emergency department with new onset hoarseness and shortness of breath. Upon further investigations, including 3-Dimensional reconstruction computerized tomography, a right subclavian pseudoaneurysm measuring 6 × 6x6 cm was discovered, which resulted in tracheal compression with subtotal obstruction. Managing the patient's airway posed significant challenges, including the risk of failed intubation, bleeding, and inability to oxygenate the patient. The case highlights the increasing importance of 3-Dimensional reconstruction computerized tomography in accurately diagnosing tracheal narrowing and compression. Furthermore, it underscores the significance of this diagnostic tool in formulating a safe and effective airway management plan. Other Information Published in: Trends in Anaesthesia and Critical Care License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.tacc.2023.101253